PENGEMBANGAN MODUL BERBASIS KONTRUKTIVISME UNTUK MATERI SEGI EMPAT DAN SEGITIGA PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VII MTsN PADANG SIBUSUK KABUPATEN SIJUNJUNG - Sari, Asma - (STKIP PGRI Sumbar, 2014)
Learning mathematics students use of on textbooks as a handbook on the learning process. However, the textbook is still difficult to understand, especially for students of class VII in rectangular and triangular material. Students have not been able to construct their own knowledge through the material in the textbook. Therefore, we need a teaching material in the form of modules that can help students to construct their thoughts using a simple mindset and easy to understand students. This type of research is the research and development. The design of the study is a 4-D model consisting of stages define, design, develop, disseminate. But the stage is passed in this study only up to the stage of develop. Analysis was performed descriptively with the validation results are very valid. Having obtained a valid module then the module tested. The results of the analysis of test shows a very practical module. This means that the module-based constructivism for rectangular and triangular material in mathematics instructional class VII MTsN Padang Sibusuk, Sijunjung district has been used as a valid and practical teaching materials.